Introduction to environmental engineering - Vesilind, P. Aarne (Boston, MA : PWS, 1997)
This book is divided into two parts: Fundamentals and Applications of Environmental engineering.
Keywords: Environmental engineering; Environmental ethics; Environmental engineering; Environmental ethics